1999
DOI: 10.5914/tropocean.v27i1.2777
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfométrica do camarão Sete-Barbas, Xiphopenaeus kroyeri (Heller, 1862), (Crustacea: Decapoda: Penaeidae), capturado no Nordeste do Brasil.

Abstract: RESUMOA pesca artesanal de camarão com barcos motorizados na região Nordeste do Brasil teve inicio em 1969, na área de pesca em frente ao Pontal do Peba (estado de Alagoas), expandindo-se posteriormente por outras áreas da plataforma continental, entre os estados do Maranhão e Bahia. O camarão setebarbas, Xiphopenaeus kroyeri (HELLER, 1862), é a espécie mais abundante entre os peneídeos capturados na região, alcançando a média de 70,0% dos desembarques. No presente trabalho são apresentadas algumas medidas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The slope b estimated for males was higher than for females both before and after the inflexion point (CL i ). Several authors found the same pattern of higher slope for males in other areas (Ivo & Santos, 1999;Natividade, 2006;Martins et al, 2013). This change in slope may be associated with the length at first maturity for both sexes, as it is observed after the first maturity.…”
Section: Discussionmentioning
confidence: 63%
“…The slope b estimated for males was higher than for females both before and after the inflexion point (CL i ). Several authors found the same pattern of higher slope for males in other areas (Ivo & Santos, 1999;Natividade, 2006;Martins et al, 2013). This change in slope may be associated with the length at first maturity for both sexes, as it is observed after the first maturity.…”
Section: Discussionmentioning
confidence: 63%